Job Demands and Resources in Distant Working Conditions and Their Impact on Emotional Well-being: Evidence from a Longitudinal Study of Healthcare Workers - Zeng, W.L.; Ma, S. (EURAM 2024 Conference, 2024)
Background/objective: Working independently from various locations is becoming a natural part of the occupational landscape for employees. However, little is known about the job demands and resources in distant working settings shape employee’s well-being. This study aims to investigate how job demands, job resources and work-family conflict affect employee’s emotional well-being and their emotions development over time with a sample of Chinese healthcare workers working away from their hospital and home during the COVID-19 pandemic. Methods: Using multi-wave longitudinal data collected from three batches of anti-COVID-19 mission healthcare workers (n = 139), we examined the relationship between workload and perceived risks as job demands and social support as job resources and emotional well-being, as well as the moderating effect of work-family conflict on the above relationships. Data were analyzed using hierarchical linear modeling (HLM). Results: We found that a) the baseline level of positive emotions and negative emotions predicted increase in positive emotions and negative emotions over time, respectively; in addition, days predicted an increase in positive emotions and a moderate decrease in negative emotions over time; b) job demands (workload, perceived risks) predicted increase in negative emotions over time while job resources (social support) predicted increase in positive emotions and decrease in negative emotions over time; c) work-family conflict played a vulnerability role on emotional well-being. Conclusion: These findings advance our understanding of the mental health functioning and development of employees in distant working condition and enrich the literature of Job Demands-Resources model with intensive longitudinal data from a unique occupational group working in distant working environment.